Change Of Leaders Affects Stock Prices - Rahmayani, Aprilia; Herlinda Maya Kumala Sari; Sriyono (Politeknik Piksi Ganesha Indonesia, 2025)
This study aims to provide additional insights into Return On Equity, Total Asset Turnover, and Earnings Per Share, and their impact on stock prices, which have been listed on the IDX from 2021 to 2023. The research utilizes a quantitative method as the collected data is converted into numerical form. The study uses 41 samples based on purposive sampling. Muhammadiyah University Sidoarjo provides the Indonesia Stock Exchange investment gallery along with its data, and E-Views 12 software is used to process the data. In conclusion, the data used in this study does not have a significant partial effect on stock prices. However, Earnings Per Share has an impact on stock prices when considered separately. This study is limited by its focus on only three financial indicators and a three-year period from 2021 to 2023. Additionally, it highlights that other factors, beyond the scope of the variables studied, may influence stock prices. Future research should explore additional variables, such as macroeconomic factors and industry-specific elements, to provide a more comprehensive understanding. The insights from this study emphasize the importance of EPS in stock price evaluations, particularly for investors focusing on profitability indicators.